2010
DOI: 10.1007/s11242-010-9580-1
|View full text |Cite
|
Sign up to set email alerts
|

Darcy–Brinkman Flow Through a Corrugated Channel

Abstract: A perturbation analysis is carried out to the second order to give effective equations for Darcy-Brinkman flow through a porous channel with slightly corrugated walls. The flow is either parallel or normal to the corrugations, and the corrugations of the two walls are either in phase or half-period out of phase. The present study is based on the assumptions that the corrugations are periodic sinusoidal waves of small amplitude, and the channel is filled with a sparse porous medium so that the flow can be descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The opposite is true forδ ⊥ eff . This finding concurs with that of Wang (1976Wang ( , 1979 and Ng and Wang (2010), who found that the resistance to flow between two corrugated plates depends on the flow direction as well as on the phase of the corrugations. Slip length is the distance by which the no-slip plane is shifted outward from the physical wall.…”
Section: Effective Slip Lengths and The Phasesupporting
confidence: 92%
“…The opposite is true forδ ⊥ eff . This finding concurs with that of Wang (1976Wang ( , 1979 and Ng and Wang (2010), who found that the resistance to flow between two corrugated plates depends on the flow direction as well as on the phase of the corrugations. Slip length is the distance by which the no-slip plane is shifted outward from the physical wall.…”
Section: Effective Slip Lengths and The Phasesupporting
confidence: 92%
“…Chu [41] studied the slip flow in an annulus with corrugated walls. Ng and Wang [42] discussed the effects of both longitudinal and transverse wall corrugations on the [43] discussed the effects of near-wall slip induced by surface roughness on the pressure rise and flow rate of a single rotating-disk viscous micropump operating with Newtonian water. Wang [44] studied the low Reynolds number flow in a tube with helical corrugations.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are utilizing this model to discuss the behaviour of viscous fluid flows in porous regions e.g. [8][9][10][11]. Lately, the most important boundary condition that has widely used is the stress jump condition on a porous-fluid interface developed by OchoaTapia and Whitaker [12,13].…”
Section: Introductionmentioning
confidence: 99%